2021
DOI: 10.1097/j.jcrs.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Call to action: treating dry eye disease and setting the foundation for successful surgery

Abstract: This review discussed the predisposing and exacerbating factors for DED and the importance of adequately treating DED prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…A compromised ocular surface and punctate erosions of the cornea may lead to inaccurate biometry measurements before the procedure and postoperative dissatisfaction. [5][6][7][8][9] The ESSENCE-2 study demonstrated superiority to vehicle in the primary sign end point tCFS score at day 29, thereby confirming ESSENCE-1 results. 16 In addition, the onset of effect in tCFS reached statistical significance at day 15, which is substantially faster than reported results with other products used for the treatment of DED.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…A compromised ocular surface and punctate erosions of the cornea may lead to inaccurate biometry measurements before the procedure and postoperative dissatisfaction. [5][6][7][8][9] The ESSENCE-2 study demonstrated superiority to vehicle in the primary sign end point tCFS score at day 29, thereby confirming ESSENCE-1 results. 16 In addition, the onset of effect in tCFS reached statistical significance at day 15, which is substantially faster than reported results with other products used for the treatment of DED.…”
Section: Discussionmentioning
confidence: 64%
“…The importance of this is that many of these patients are candidates for cataract surgery. A compromised ocular surface and punctate erosions of the cornea may lead to inaccurate biometry measurements before the procedure and postoperative dissatisfaction …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50] External and Behavioral Factors Several external factors have been linked to DED, including use of contact lenses and certain ocular medications. 6,[51][52][53][54] Identification of these factors, specifically the patient's medical and ocular history, is important because it allows for modifications that may improve the patient's DED. For example, use of topical antiglaucoma medications has been associated with DED, 52,53,55,56 which may be caused by preservatives such as benzalkonium chloride.…”
Section: Inflammation In Dry Eye Diseasementioning
confidence: 99%